ISOLASI, IDENTIFIKASI DAN UJI AKTIVITAS ANTIOKSIDAN SENYAWA FLAVONOID DAUNBINAHONG (Anredera cordifolia (Ten.) Steenis) - Rahmawati, Lina (Chem Info Journal, 2013)
Binahong  (Anredera  cordifolia  (Ten.)  Steenis)  can  heal  burns,  wounds  like  after  the surgery, rheumatoid arthritis, gout, heart swelling, typhoid, and stroke. Binahong leaves contain flavonoid  compound  that  has  an  antioxidant  activity.  The  aims  of  this  research  are  isolation, identification, and antioxidant activity  test of  flavonoid compound  from Binahong  leaves. This research  was  started  by  extraction,  partition,  purification,  and  followed  by  the  purity  test. Identification  of  flavonoid  structure  was  conducted  using  shift  reagent  on  UV-Vis spectrophotometer. Antioxidant  activity  test  used DPPH method, which  brings  in  the  value  of IC50.  Characterization  by  shift  reagents  on  UV-Vis  spectrophotometer  resulted  that  the compound was 3, 5, 3’,4’-  tetrahydroxiflavonol. The results of antioxidant activity  test  indicate that ethyl acetate extract and C fraction from Binahong leaves have a potentiality as antioxidant.